Fit-testing procedures of selected manufacturing companies in Metro Manila - Ferrer, Mary Patrick Lorenzo
This study sought to determine the measurement specifications, silhouette, fit and specific problems encountered in fit testing procedures for straight leg denim jeans of selected manufacturing companies in Metro Manila. This descriptive-qualitative research utilized convenience sampling in the selection of its respondents. The respondents of the study were ten (10) garment-manufacturing companies of jeans locally sold. Instrumentation for the study included questionnaires, interviews, and a measurement survey. Questions were formulated based on the study of fit testing procedures conducted by Bye and LaBat (2005). The data were presented in tabular form with descriptive and qualitative analysis. The results of the study showed that majority of the respondents use similar fit testing procedures. Two out of ten respondents used a distinct procedure called the wear testing procedure. The study revealed that none of the respondents use a standard dress form to fit straight leg jeans. The fit testing procedures used by the respondents were determined by the basic objectives undertaken by these companies and brand to improve quality of fit and workmanship. The most common problems encountered by the respondents in fit testing of straight leg denim jeans were: (1) their fitters do not retain in their specific jeans label, (2) their jeans do not fit adequately on their customers because they have different size specifications, and (3) they have no standard model. The study will contribute knowledge on how these companies do fit testing procedures, fit concerns and specific problems for fit testing of straight leg denim jeans.